2017
DOI: 10.1002/soej.12247
|View full text |Cite
|
Sign up to set email alerts
|

The Gender Gap in Economics Degrees: An Investigation of the Role Model and Quantitative Requirements Hypotheses

Abstract: Using a panel of 159 institutions over 10 years, we investigate the role model effect of women faculty and quantitative requirements on the female proportion of undergraduate economics majors. We find no evidence that female faculty attract female students. Calculus, however, does matter. A one semester calculus requirement is associated with more female majors at institutions offering business degrees and liberal arts colleges. A second semester calculus requirement deters women from majoring in economics at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 39 publications
1
18
0
Order By: Relevance
“…Because the number doctorates awarded to Blacks in mathematics exceeds the number awarded in economics, I have argued that mathematical ability is not a hindrance for Black to complete degrees in economics (Sharpe, 2017). This is consistent with findings of Emerson, McGoldrick, and Sigfried (2018) that higher math requirements may lead to an increase in the number of female economics majors at liberal arts colleges and institutions that offer a business degree.…”
Section: The Pipelinesupporting
confidence: 90%
“…Because the number doctorates awarded to Blacks in mathematics exceeds the number awarded in economics, I have argued that mathematical ability is not a hindrance for Black to complete degrees in economics (Sharpe, 2017). This is consistent with findings of Emerson, McGoldrick, and Sigfried (2018) that higher math requirements may lead to an increase in the number of female economics majors at liberal arts colleges and institutions that offer a business degree.…”
Section: The Pipelinesupporting
confidence: 90%
“…Therefore, they conclude that they find no evidence for a peer mentoring effect. Finally, Emerson, McGoldrick, and Siegfried (2018) find no link between the choice of a female student choosing to major in economics and having female professors.…”
Section: Prior Literaturementioning
confidence: 75%
“…Currently, the economics profession is struggling to attract women into the profession. Emerson et al (2018) highlight the difficulty in recruiting young women into the field. But, they focus on students who intend to become professional economists.…”
Section: Conclusion and Suggestions For Future Researchmentioning
confidence: 99%
“…The authors found no relationship between faculty gender composition and the students' choice of major. Emerson et al (2018), Smith and Zenker (2014) examined whether female faculty role models had a positive effect on female students' choice of economics as a major. Their results showed no support for the female faculty role model effect.…”
Section: Role Model Effectmentioning
confidence: 99%